Mechanism of field-induced unwinding of SmC* helix and biasfield dependencies of dielectric permittivity and effective polarization - VIJ, JAGDISH; SONG, JANG-KUN; MANNA, UTTAM (My University, 2008)
We propose an unwinding model based on helical fractures confirmed by spectroscopic and microscopic observations. This model combined with the fixed helical pitch can explain the various physical phenomena observed in SmC? phase of ferroelectric liquid crystals. These are the dc field dependencies of i) dielectric strength, ii) relaxation frequency of the Goldstone mode, and iii) the effective polarization. The conventional diverging pitch model where the helical pitch increases with an increase in the field is shown not to satisfactorily explain these observations.
PUBLISHED
Article number 26003 5pgs
Keywords: Physics; Continuum models and theories of liquid crystal structure